Robot Lengan Pemindah Barang Otomatis Berbasis Arduino Menggunakan Sensor Warna: Automatic Arduino-Based Robot Arm Shifters Using Color Sensors - Sumardi, Sumardi (Jurnal Sains Komputer dan Teknologi Informasi, 2018)
Robot arm transporter using Arduino-based sensor auto color, a tool designed to this aim to reduce human role in a grouping or sorting goods with the sort tool so that it can minimize the influence of inconsistencies humans in the event. This tool as well as a simulation as well as the media of instruction. Methods of data analysis used IE needs analysis that includes software that is the OS, and the Arduino Software, and hardware in the form of a Laptop, Arduino, Sensor, RGB, and Servo Motor. From the results of testing that has been done can be inferred that this Robot can run well at a time when reading the color box and put the table by the location of their vessels. The conclusion of the tool is designed as a common transport good; the robotic arm can be applied using several servos in the number of dof.